2010
DOI: 10.1146/annurev-immunol-030409-101305
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated View of Humoral Innate Immunity: Pentraxins as a Paradigm

Abstract: The innate immune system consists of a cellular and a humoral arm. Pentraxins (e.g., the short pentraxin C reactive protein and the long pentraxin PTX3) are key components of the humoral arm of innate immunity which also includes complement components, collectins, and ficolins. In response to microorganisms and tissue damage, neutrophils, macrophages, and dendritic cells are major sources of fluid-phase pattern-recognition molecules (PRMs) belonging to different molecular classes. Humoral PRMs in turn interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
654
1
23

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 539 publications
(689 citation statements)
references
References 130 publications
11
654
1
23
Order By: Relevance
“…CRP binds to apopDNA and promotes macrophage-mediated apopDNA uptake Accumulating data indicate that CRP has the capacity of binding to nuclear antigen (Garlanda et al, 2005;Bottazzi et al, 2010). To assess the binding ability of CRP to apopDNA, we performed dot blot analysis and found that CRP could bind to apopDNA (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CRP binds to apopDNA and promotes macrophage-mediated apopDNA uptake Accumulating data indicate that CRP has the capacity of binding to nuclear antigen (Garlanda et al, 2005;Bottazzi et al, 2010). To assess the binding ability of CRP to apopDNA, we performed dot blot analysis and found that CRP could bind to apopDNA (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, C-reactive protein (CRP), a member of the pentraxin family with an ability to bind to nuclear antigens as well as to damaged membranes and microbial antigens (Du Clos, 1989), was found to play a key role in the protection from autoimmune disease (Ogden and Elkon, 2005;Rodriguez et al, 2005;. Moreover, CRP was a prototypic acute phase protein produced mainly in response to inflammation, infection, or tissue damage (Garlanda et al, 2005;Bottazzi et al, 2010) and was reported to recognize nuclear autoantigens released from apoptotic cells, opsonize them through interacting with cell-surface FcγR, thereby activating macrophage-mediated phagocytosis (Mold et al, 2001;Bottazzi et al, 2010). In addition to activating phagocytosis through FcγR, emerging evidence demonstrated that CRP could also regulate immune responses (Marjon et al, 2009), indicating that CRP could modulate nuclear antigen-mediated immune response.…”
Section: Introductionmentioning
confidence: 99%
“…As such, the low expression level of CRP under normal physiological conditions and during the early phases of inflammation would restrict its major contribution to the late stages of tissue injury or infection. This appears to be incompatible with the proposed function of CRP in the non-inflammatory clearance of apoptotic cells in times of health and disease [75] and its role as a component in the innate immunity and host defense [1,3]. In this regard, the rapid formation of mCRP m can override the size limitation such that even the dissociation of a single CRP molecule can provide multi-point binding to, for example, activate C1q.…”
Section: Dissociation Of Crp Localizes the Enhanced Bioactivitiesmentioning
confidence: 99%
“…Ligand-bound CRP can further interact with C1q via its effector face to activate the classical complement pathway (CCP). Therefore, CRP is considered to act as a pattern recognition receptor in innate immunity, facilitating the efficient clearance of harmful materials [3]. Moreover, the effector face of CRP appears to also possess binding sites for cell surface receptors, including FcγR [4,5], Figure 1 The X-ray crystal structure of CRP in complex with phosphocholine.…”
mentioning
confidence: 99%
See 1 more Smart Citation